Upaya Mereduksi Prokrastinasi Akademik pada Siswa dengan Konseling Behavioristik Teknik Kontrak Perilaku - Isnaini, Isnaini; Anas, Muhammad; Harum, Akhmad (Universitas Negeri Makassar, 2023)
The purpose of this study was to describe academic procrastination and efforts to overcome it using a behavioristic approach with behavior contracting techniques for students at SMAN 5 Kundur. This research uses a qualitative approach with a case study method. The subjects of this study consisted of two 11th grade students of SMAN 5 Kundur who were indicated to have a high level of academic procrastination. The data analysis used is qualitative data analysis which consists of three stages, namely, data reduction, data exposure and conclusions. The results of this study indicate that individual counseling services with a behavioristic approach to behavior contracting techniques can reduce the level of academic procrastination in students.